Exploring Gendered Voices against Racial Discrimination in Angelou and Hughes’s Poems: An Analysis of Transitivity - Dr. Mamona Yasmin Khan; Mahnoor Zahra (Research Journal of Psychology, 2025)
In this study, the researcher has conducted the transitivity analysis of Angelou and Hughes’s poems that portray the theme of racial discrimination. By conducting the transitivity analysis of the selected poems of African-American writers, the researcher has compared the types of process, participants, and circumstances that are represented in the poems of writers of two opposite gender. Therefore, the researcher has conducted a comparative analysis of the poems of male and female writers who have written on the same subject of racial discrimination through transitivity system. This research has the objectives, to find out the difference in the process types in the poems of Angelou and Hughes and the way they have used the subject of racial discrimination through transitivity analysis. The data for this research paper have been two poems: I, Too (1926) and Little Old Letter (n.d.) by Hughes and the two other poems, I Know Why the Caged Bird Sings (1983) and Africa (n.d.) by Angelou. The researcher has conducted a mixed method study by doing both qualitative and quantitative data analysis. This research paper has substantiated with the common elements of transitivity explained in An Introduction to Functional Grammar (1994) by M A K Halliday and An Introduction to Systemic Functional Linguistics (2004) by Suzanne Eggins. The researcher has suggested that there are still so many complexities in the selected poems that other researchers can explore. Future researchers can compare more poems of Angelou and Hughes or other poets from different perspective.